PENGARUH MOTIVASI BERPRESTASI, POWER TUNGKAI, DAN KELINCAHAN, TERHADAP KETERAMPILAN LAY-UP SHOOT DALAM PERMAINAN BOLA BASKET - Kristalistianto Kristalistianto (Universitas Singaperbangsa Karawang, 2020)
This study aims to determine the influence of achievement motivation, leg power, and agility towards lay-up shooting skills in basketball game. The research uses the path analysis method. The results of small group trials for the achievement motivation questionnaire instrument for 89 statements were declared valid from 116 statements, for leg power instruments using the Vertical Jump Test, for agility instruments using the Illinois Agility Test, and for the Lay-Up Shooting instrument of the 7 stages tested all were declared valid, All instruments have been validated by an expert and declared Valid. For the results of testing large groups stated achievement motivation (X1) significantly influenced the lay-up shooting skill (Y) with a contribution of 33.4%, leg power (X2) significantly influenced the lay-up shooting skill (Y) with a contribution of 24.2%, agility (X3) has a significant effect on lay-up shooting skills (Y) with a contribution of 27.3%, achievement motivation (X1) has a significant effect on leg power (X2) with a contribution of 97.8, achievement motivation (X1) has a significant effect on agility ( X3) with a contribution of 95.4%, leg power (X2) has a significant effect on agility (X3) with a contribution of 90.1%. It was concluded that achievement motivation, leg power, and agility had an influence on lay-up shooting skills in basketball.